Critical Success Factors on the Implementation of Industrialized Building System in West Sumatra. Issue 1 (May 2020) - Alzahri,; Zin, R M; Farni, I; Zainuddin, M; Edrizal,
Abstract: The construction industry in West Sumatra, Indonesia is experiencing a serious challenge since the occurrence of the devastating earthquake in September 2009. The Infrastructures including residential housing, government offices, roads and bridges were damaged and destroyed. The major problems facing the construction industry is mostly related to poor planning, lack of standards for quality project implementation and poor processing time. One of the possible solutions to answer these problems is by introducing Industrialized Building System (IBS) in the construction industry. The aim of the study described in this paper is to identify the critical success factors (CSF) for the successful implementation of IBS in West Sumatra. The main methodology involved questionnaire survey to various stakeholders of the construction industry who have had experience dealing with IBS construction methods. The results and findings reveal that there are twenty-two critical success factors that need to be considered by the industry in order to ensure the success of IBS implementation. The factors can be grouped into several distinct classifications. It is expected that the findings form this study serve as a gateway for encouragement towards proper implementation of IBS in West Sumatra.